Synthesis, Characterization, Solvatochromic Properties, and Antimicrobial‐radical Scavenging Activities of New Diazo Dyes Derived from Pyrazolo[1,5‐a]pyrimidine - Şener, Nesrin; Erişkin, Selinay; Yavuz, Serkan; Şener, İzzet (Wiley, 2017)
5‐Amino‐3‐methyl‐4‐phenylazo‐1H‐pyrazole and ethyl cyanoacetate reacted in solvent‐free media at 150°C to produce 7‐amino‐3‐phenylazo‐2‐methyl‐4H‐pyrazolo[1,5‐a]pyrimidine‐5‐one (3). A series of aromatic amines was coupled using this compound (3) and nitrous acid to produce new pyrazolo[1,5‐a] pyrimidine derivatives with two arylazo groups 4(a‐m). The structures of these dyes were determined via UV–vis, Fourier transform infrared, proton nuclear magnetic resonance, high‐resolution mass spectral data, and elemental analysis. After synthesis, the solvent and acid–base effects of the dyes were investigated within the UV–vis region. The antimicrobial properties of the dyes were also studied. All dyes exhibited activity against Gram‐positive and Gram‐negative bacteria, and even against fungi. The results were compared to conventional reference results from the antibiotics ciprofloxacin and ketoconazole. Antioxidant potentials were analyzed using in vitro antioxidant models on the basis of DPPH (1,1‐diphenyl‐2‐picrylhydrazyl) radical scavenging activities. Most of the compounds exhibited excellent antioxidant activities. In particular, compound 4b had a higher activity than Vitamin C.
Keywords: i mino 3 phenylazo 6 (3' methylphenylazo) 2 methyl 4h pyrazolo[1,5 a]pyrimidine 5 one; imino 2 methyl 3,6 diphenylazo 6,7 dihydro 1h pyrazolo[1,5 a]pyrimidine 5 one; antioxidant; in vitro study; ketoconazole; ultraviolet spectroscopy; antioxidant activity; Gram negative bacterium; proton nuclear magnetic resonance; i mino 3 phenylazo 6 (2' methylphenylazo) 2 methyl 4h pyrazolo[1,5 a]pyrimidine 5 one; Article; i mino 3 phenylazo 6 (4' methylphenylazo) 2 methyl 4h pyrazolo[1,5 a]pyrimidine 5 one; i mino 3 phenylazo 6 (2' chlorophenylazo) 2 methyl 4h pyrazolo[1,5 a]pyrimidine 5 one; ciprofloxacin; Gram positive bacterium; i mino 3 phenylazo 6 (3' nitrophenylazo) 2 methyl 4h pyrazolo[1,5 a]pyrimidine 5 one; azo dye; controlled study; infrared spectroscopy; mass spectrometry; pyrazolo[1,5 a]pyrimidine derivative; antimicrobial activity; nonhuman; i mino 3 phenylazo 6 (3' chlorophenylazo) 2 methyl 4h pyrazolo[1,5 a]pyrimidine 5 one; fungus; elemental analysis; i mino 3 phenylazo 6 ( 3' methoxyphenylazo) 2 methyl 4h pyrazolo[1,5 a]pyrimidine 5 one; i mino 3 phenylazo 6 ( 2' methoxyphenylazo) 2 methyl 4h pyrazolo[1,5 a]pyrimidine 5 one; unclassified drug; antiinfective agent; drug structure; i mino 3 phenylazo 6 (4' methoxyphenylazo) 2 methyl 4h pyrazolo[1,5 a]pyrimidine 5 one; i mino 3 phenylazo 6 (4' nitrophenylazo) 2 methyl 4h pyrazolo[1,5 a]pyrimidine 5 one; i mino 3 phenylazo 6 (2' nitrophenylazo) 2 methyl 4h pyrazolo[1,5 a]pyrimidine 5 one; i mino 3 phenylazo 6 (4' chlorophenylazo) 2 methyl 4h pyrazolo[1,5 a]pyrimidine 5 one; DPPH radical scavenging assay; drug synthesis; ascorbic acid; 3. Good health